Analysis of connected seismic events using methods of the theory of digraphs - V.B. Spirtus (Геофизический журнал, 2013)
For samples from the earthquakes catalogues with large seismic events the components of unilateral relatedness of corresponding orgraphs are studied. Definition of new mathematical adjectives is proposed — octopusindex of orgraph vertexes. Dynamics of this value changes can be used in algorithms of mediumterm forecast. Test examples and results of test calculations for the earthquakes of North California and the CrimeanBlack Sea region have been given.